2012
DOI: 10.1016/j.progpolymsci.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Alginate: Properties and biomedical applications

Abstract: Alginate is a biomaterial that has found numerous applications in biomedical science and engineering due to its favorable properties, including biocompatibility and ease of gelation. Alginate hydrogels have been particularly attractive in wound healing, drug delivery, and tissue engineering applications to date, as these gels retain structural similarity to the extracellular matrices in tissues and can be manipulated to play several critical roles. This review will provide a comprehensive overview of general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
4,340
1
45

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 6,364 publications
(4,419 citation statements)
references
References 185 publications
33
4,340
1
45
Order By: Relevance
“…Our results revealed that after immersion of crosslinked alginate hydrogels into cell culture medium the hydrogels' storage modulus decreased from 95 kPa (day 1) to approximately 19 kPa on day 7 ( Figure S3a). 34 This could be explained by ionic exchange between calcium and monovalent ions (such as sodium ions). However, this tendency seemed to be reversed by a possible continuation of the crosslinking, by adding calcium ions to the medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results revealed that after immersion of crosslinked alginate hydrogels into cell culture medium the hydrogels' storage modulus decreased from 95 kPa (day 1) to approximately 19 kPa on day 7 ( Figure S3a). 34 This could be explained by ionic exchange between calcium and monovalent ions (such as sodium ions). However, this tendency seemed to be reversed by a possible continuation of the crosslinking, by adding calcium ions to the medium.…”
Section: Resultsmentioning
confidence: 99%
“…This happens due to the release of calcium ions into the surrounding media caused by the exchange with monovalent cations (such as sodium ions present in the medium). 34 This could be either an advantage (enabling cell release from the hydrogel) or a disadvantage (when long-term cultivation is required). To address this problem, we supplemented the culture medium with 1% (v/v) solution of CaCl 2 ( Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the reloading curves in DN gels follow the previous unloading curve indicating the permanent nature of the damage occurring in these covalently crosslinked gels. The high toughness and mechanical recoverability of the hybrid gel system originates from the ionic crosslinks, where the guluronic units (also known as G group) on the alginate chains are associated by Ca 2+ ions to form a zip-like junction described by a socalled "egg-box" model [10][11][12][13]. When a hybrid gel is subject to external force the crosslinks are "unzipped", dissipating dissociation energy of the ionic bonds and entropic energy of the loaded network strands.…”
mentioning
confidence: 99%
“…Cells of the hepatic cell line Hepg2 were printed with alginate as the crosslinking agent, but cell viability was reduced when a high‐extrusion pressure from the printing device was applied 28. Because alginate is characteristically bioinert to mammalian cells and therefore not supportive of cell differentiation and survival, other biomaterials have been explored 29. For example, the use of gelatin as a base material ensures the control of ink thickness and higher printability 27.…”
Section: Implantable Technologies For Liver Therapiesmentioning
confidence: 99%